2000
DOI: 10.1038/sj.bmt.1702337
|View full text |Cite
|
Sign up to set email alerts
|

Mixed chimerism in the B cell lineage is a rapid and sensitive indicator of minimal residual disease in bone marrow transplant recipients with pre-B cell acute lymphoblastic leukemia

Abstract: Summary:One of the major problems after allogeneic bone marrow transplantation (BMT) is a high frequency of leukemia relapse. We have prospectively studied the presence of donor-and recipient-derived chimeric cells in bone marrow recipients with pre-B cell acute lymphoblastic leukemia (pre-B-ALL). The chimeric status of BMT recipients was compared to minimal residual disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…We have previously shown, by reducing the irrelevant background, that the sensitivity is increased by two logs when CD19 + cells are analyzed separately in patients with pre-B-ALL and B-CLL after SCT. 34,35 This has also been found by others. [44][45][46] Thiede and co-workers 47 have also recently shown that high sensitivity may be achived after cell separation of CD34 + cells, thus enabling early detection of leukemia relapse after SCT.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We have previously shown, by reducing the irrelevant background, that the sensitivity is increased by two logs when CD19 + cells are analyzed separately in patients with pre-B-ALL and B-CLL after SCT. 34,35 This has also been found by others. [44][45][46] Thiede and co-workers 47 have also recently shown that high sensitivity may be achived after cell separation of CD34 + cells, thus enabling early detection of leukemia relapse after SCT.…”
Section: Discussionsupporting
confidence: 85%
“…This has also been proposed by others. 35,44 In conclusion, analysis of MC in the leukemia-affected cell lineage of patients with AML and MDS is a sensitive and specific method which enables early detection of leukemia relapse after allogeneic SCT. This study may provide a rational basis for treatment with adoptive immunotherapy at an earlier time after SCT than at present, in order to treat recurrences of malignant disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…119 In ALL patients, several studies have been performed evaluating the impact of mixed chimerism after enrichment of the cell population carrying the leukemic phenotype (possible targets could be: CD10, CD19, CD34 for precursor B-ALL, CD3, CD4, CD5 and CD8 for T-lineage ALL). 28,[120][121][122][123] These studies showed a remarkable correlation between minimal residual disease and mixed chimerism in the respective subset. However, large studies in ALL patients, indicating the predictive value of mixed chimerism in different subsets for the individual patient with regard to disease recurrence, are yet missing.…”
Section: Chimerism In Malignant Diseasesmentioning
confidence: 99%
“…A large number of papers have been published using different technologies 1,3,6,8,[15][16][17][18] (probably too many from a personal viewpoint) and in certain forms of leukaemia and aplastic anaemia, relevant studies have attempted to tease out the relevance of complete donor chimerism, mixed chimerism (stable, transient and progressive) in the context of relapse, graft rejection and risk of GVHD. [1][2][3][4][5][6][7][8][9][19][20][21][22] The time is now ripe to standardise approaches to (1) sample collection, allowing for selection of specific cell lineages which are becoming increasingly relevant in relapse prediction, 23,24 (2) timing of chimerism analysis (which will be undoubtedly critical for prospective studies), chimerism technology (which should probably be PCR based, relying either on established short tandem repeat or variable number tandem repeat PCR used by many of the most active laboratories in this area, or by adapting real time PCR approaches or other methodologies for truly quantitative assessment of chimerism post allogeneic SCT). Molecular diagnostic development on a Europe-wide basis has been employed extremely successfully in BIOMED and Europe Against Cancer Consortia for the establishment of standardised assays for assessment of minimal residual disease in childhood acute lymphoblastic leukaemia, either using RQ-PCR of specific chromosomal translocations 25 or real time PCR approaches for T cell receptor and immunoglobulin gene rearrangement assays 26 and a similar approach to standardisation in chimerism analysis will allow the development of large-scale prospective studies with sufficient statistical power to provide the relevant data for clinical intervention.…”
mentioning
confidence: 99%